Analisis peningkatan kinerja pemeliharaan mesin dengan Total Productive Maintenance (TPM) pada mesin boiler pabrik kelapa sawit PT.Multi Karya Persada Indonesia Di Kabupaten kapuas Kalimantan Tengah - Abdul Rahman (LPPM Swadaya Institute of Business and Communication, 2022)
The implementation of Total Productive Maintenance (TPM) is to improve maintenance performance in the production machine at PT. Multi Karya Persada Indonesia In Kapuas Regency, Central Kalimantan This is descriptive research. The analysis used overall equipment effectiveness (OEE), OEE six big losses, Pareto diagrams, and cause and effect diagrams. As a result of PTPN VI PT. Multi Karya Persada Indonesia In Kapuas Regency, Central Kalimantan had a problem with machine performance value, it was lower than the world-class standard of about 71.85% (≤ 95%). Caused of the low OEE value (65,16%) is high idling and minor stoppages and reduced speed losses value. To improve this problem the company is implementing TPM, with planning 8 TPM pillars as the foundation for implementing TPM.